Effect of silencing Thrips palmi Btk29A and COL3A1 on fitness and virus acquisition - Rajesh, Vavilapalli; Jangra, Sumit; Ghosh, Amalendu (Frontiers in Microbiology, 2023)
Thrips palmi (Thysanoptera: Thripidae) is a major agricultural pest infesting over 200 plant species.Along with direct injury caused by feeding, T. palmi spreads several orthotospoviruses. Groundnut bud necrosis orthotospovirus (GBNV, family Tospoviridae, genus Orthotospovirus) is the predominant orthotospovirus in Asia, vectored by T. palmi. It is responsible for almost 89 million USD losses in Asia annually. Several transcripts of T. palmi related to innate immune response, receptor binding, cell signalling, cellular trafficking, viral replication, and apoptosis are responsive to the infection of orthotospoviruses in thrips. Expression of T. palmi tyrosine kinase Btk29A isoform X1 (Btk29A) and collagen alpha-1(III) chain-like (COL3A1) are significantly regulated post-GBNV and capsicum chlorosis orthotospovirus (CaCV) infection. In the present study, T. palmi Btk29A and COL3A1 were silenced and the effect on virus titer and fitness was assessed. The expression of Btk29A and COL3A1 was significantly reduced by 3.62 and 3.15-fold, respectively 24 hrs post-dsRNA exposure. Oral administration of Btk29A and COL3A1 dsRNAs induced 60% and 50.9% mortality in T. palmi. The GBNV concentration in T. palmi significantly dropped post-silencing Btk29A. In contrast, the silencing of COL3A1 led to an increase in GBNV concentration in T. palmi compared to the untreated control.This is the first report on the effect of silencing Btk29A and COL3A1 on the fitness and GBNV titer in T. palmi.